ANALYSIS OF IMMIGRATION MANAGEMENT INFORMATION SYSTEM (SIMKIM) VERSION 2.0 FOR THE ISSUANCE OF A RESIDENCE PERMIT WITH THE COBIT 5 METHOD AT THE CLASS I IMMIGRATION OFFICE TPI MAKASSAR - Andi Hammam Alfarisi Akasy (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
Along with the advancement of information technology, the Directorate General of Immigration has integrated all immigration functions through SIMKIM since 2007. Immigration Management Information ‘System (SIMKIM) is a system used to collect, process and convey information to support operations, management, and policy making. Simkim implementation in the Immigration Technical Implementation Unit is one of them by ope rating the system in the process of issuing residence permits to Foreigners. The arrival of Foreigners through immigration checkpoints by remembering selective policy strategies, only foreigners who can benefit and do not interfere with the security or order of the public can enter and live in the Territory of Indonesia. The purpose of this study is to analyze the implementation of simkim version 2.0 use at TPI Makassar Class I Immigration Office. This research uses qualitative descriptive methods with the COBIT 5 (Control Objective for Information and Related Technology) model, while the data source is used namely primary and secondary data obtained by interview, document study and observation. The theoretical foundations used are information technology theory, management information systems, public service and information technology governance. Based on the analysis of data conducted, it was concluded that in terms of the process of issuing residence permits using SIMKIM Version 2.0 there are still various obstacles both from the system and in terms of facilities and implementation of information technology governance by measuring maturity level maturity level.